La participación partidaria y el impacto de los contextos políticos. Un estudio de biografías militantes en Jujuy - Berardi Spairani, Adrian Pablo (Universidad Nacional del Litoral, 2018)
In this article we propose observe the way in which the political cleavages influence the militant biographies; we are concerned to answer if the political context is an element to be considered for the maintenance of the militant commitment and in what form. To carry out these objectives we will analyse the trajectories of two-party militants who began their political participation in the decade of the 2000 , recovering the career perspective proposed by Howard Becker, considering the trajectory as a model of orderly sequences of social behaviour, considering the objective and subjective aspects (the way they (la narrate their own history).